Effects of Resilience on Productivity under Authentic Leadership - Zehir, Cemal; Narcikara, Elif (ELSEVIER SCIENCE BV, 2016)
Flexible, storable and convertible dynamic capabilities ensures resilience in organizations and make them powerful in coping with problems and crises. In organizational level a resilient leadership is a prerequisite of resilient organizations. According to positive psychology and positive organizational literature authentic leadership is a suitable leadership model for resilient organizations with high levels of organizational efficiency. In this study we are specifically focusing on authentic leadership style, which is the most famous leadership style among positive organizational scholarship researchers, its effects on resilience of employees and individual productivity. (C) 2016 Published by Elsevier Ltd.
Keywords: POSITIVE EMOTIONS; ORGANIZATIONAL RESILIENCE; PSYCHOLOGICAL RESILIENCE; PERFORMANCE; RESOURCE; FUTURE; STRESS; IMPACT; Business & Economics